2006
DOI: 10.1007/s00439-006-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma polymorphisms and their interaction with smoking are associated with lung function

Abstract: Interactions between genetic and environmental determinants are likely to be important in the pathogenesis of chronic obstructive pulmonary disease. We hypothesized that interferon gamma (IFNG) single nucleotide polymorphisms (SNPs) and their interaction with smoking are associated with the rate of decline or level of lung function in smokers. We studied four SNPs in IFNG in 585 non-Hispanic whites (NHW) who had the fastest (n =280) or the slowest (n=305) decline of FEV(1)% predicted selected from among contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
3
4
1
Order By: Relevance
“…Both animal and human studies have shown increased inflammatory proteins in the presence of cigarette smoke [30], [31], [32] and prior groups have found smoking-dependent differential associations between inflammatory proteins and markers of disease severity [33]. Relevant to our finding of a direct association of IFN-γ and IL-13 with WA% in current, but not former, smokers, others have also demonstrated interactions between smoking and both IFN-γ [34] and IL-13 [35] polymorphisms in association with lung function. We have further defined specific associations with CT measures of airway thickening independent of airflow obstruction.…”
Section: Discussionsupporting
confidence: 67%
“…Both animal and human studies have shown increased inflammatory proteins in the presence of cigarette smoke [30], [31], [32] and prior groups have found smoking-dependent differential associations between inflammatory proteins and markers of disease severity [33]. Relevant to our finding of a direct association of IFN-γ and IL-13 with WA% in current, but not former, smokers, others have also demonstrated interactions between smoking and both IFN-γ [34] and IL-13 [35] polymorphisms in association with lung function. We have further defined specific associations with CT measures of airway thickening independent of airflow obstruction.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast with our previous studies,5,6 there was no association of any polymorphism with the rate of decline of lung function (Table 3). Similarly, there was no association of the polymorphisms with measures of baseline lung function in the same subset of individuals (Table 3).…”
Section: Resultscontrasting
confidence: 99%
“…All three studies have relatively small sample sizes. The associations of IL6 SNPs with FEV 1 decline in the current study are novel and are the most significant findings among all the studies we have published utilizing the LHS cohort 1316,2427. To strengthen our initial finding in the LHS, we incorporated an association study of IL6 SNPs with COPD in the NETT-NAS.…”
Section: Discussionmentioning
confidence: 77%
“…The LHS cohort provides an excellent opportunity to explore associations between gene polymorphisms and haplotypes with FEV 1 % predicted13,14 as well as the rate of decline in FEV 1 15,16. To validate novel associations between IL6 SNPs with lung function phenotypes, replication of results was sought in COPD cases from the National Emphysema Treatment Trial (NETT) with participants from the Normative Aging Study (NAS) serving as controls 17,18…”
Section: Introductionmentioning
confidence: 99%